Relevansi Pendidikan Di Era Society 5.0 Dengan Motivasi Belajar Fiqih Siswa di Kelas VII MTSN 1 Langkat - Aprida Hanum; Marhan Hasibuan; Anida Anida (Lembaga Pengembangan Kinerja Dosen, 2023)
This research is a type of quantitative research using primary data. The population in this study amounted to 200 students. The sample and sampling in this study used a non-probability sampling technique using a random sampling method with a total sample of 30 respondents. The data processing technique uses a regression test with the product moment formula. The conclusion results from the calculation of the education questionnaire in the era of society 5.0 which has a mean result of 51.9, a median of 54.8, a mode of 53.4, a variance of 26.04 and a standard deviation of 5.10 is acceptable with significant tolerance limits. This shows a positive and significant relationship. Students' motivation to study jurisprudence has an average result of 53.4, median of 53.7, mode of 53.2, variance of 18.19 and standard deviation of 4.26 and can be accepted with significant tolerance limits. This shows a positive and significant relationship. There is a positive and significant relationship between education in the era of society 5.0 and students' motivation to study jurisprudence with the regression line Y=19.76 +0.66 X There is a significant correlation between education in the era of society 5.0 with students' motivation to study jurisprudence in fiqh subjects at MTs Negeri I Langkat after the regression test was carried out using the product moment formula with a calculated result of 0.818 with a strong or high level of relationship.